Studies in history and jurisprudence - Bryce, James Bryce, Viscount, 1838-1922. (New York, Oxford university press, American branch; [etc., etc., 1901)
"None of these studies have previously appeared in print except two, viz, those relating to the United States [in Johns Hopkins university studies in historical and political science, 5th series, no. 9] and the two Dutch republics [in the Forum, April, 1896] and both of these have been enlarged and revised . Some studies were (in substance) delivered as public lectures at Oxford during the years 1870-1893."--Pref. The Roman empire and the British empire in India.--The extension of Roman and English law throughout the world.--Flexible and rigid constitutions.--The action of centripetal and centrifugal forces on political constitutions.--Primitive Iceland.--The Constitution of the United States as seen in the past.--The South African constitutions.--The constitution of the commonwealth of Australia.--Obedience.--The nature of sovereignty.--The law of nature.--The methods of legal science.--The relations of law and religion.--Methods of law-making in Rome and in England.--The history of legal development at Rome and in England.--Marriage and divorce in Roman and in English law.--Inaugural lecture.--Valedictory lecture. Mode of access: Internet.